2013
DOI: 10.1177/0269881112474524
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute systemic administration of cannabidiol on sleep-wake cycle in rats

Abstract: The systemic acute administration of CBD appears to increase total sleep time, in addition to increasing sleep latency in the light period of the day of administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 26 publications
2
41
1
Order By: Relevance
“…Concerning the effects of CBD on sleep, animal studies have found different results according to the dose and route of administration used . The intracerebroventricular administration of CBD led to an increase in wakefulness and consequent reduction in REM sleep in rats .…”
Section: What Is New and Conclusionmentioning
confidence: 99%
“…Concerning the effects of CBD on sleep, animal studies have found different results according to the dose and route of administration used . The intracerebroventricular administration of CBD led to an increase in wakefulness and consequent reduction in REM sleep in rats .…”
Section: What Is New and Conclusionmentioning
confidence: 99%
“…For instance, Monti (1977) found a diminution in sleep after systemic administration of CBD [10], whereas Carlini and Cunha (1981) showed an improvement in sleep in insomniacs after using CBD [11]. Moreover, systemic administration of CBD (10 or 40 mg/kg) in male Wistar rats during the light period, enhanced the total percentage of sleep [12]. Further complexity has been added to the understanding of CBD pharmacology since Nicholson et al .…”
Section: Modulation Of Sleep-wake Cycle By Cannabidiolmentioning
confidence: 99%
“…However, other studies have demonstrated a reduction in REM sleep following THC administration (2123). Similarly, while in some cases CBD has demonstrated hypnotic properties (24, 25), it has alternatively been associated with increased wakefulness (26). Furthermore, chronic cannabis users exhibit decreased SWS compared to controls immediately following termination of use, with recovery after fours weeks of abstinence (27).…”
Section: Introductionmentioning
confidence: 99%